Revisiting the Null Subject Parameter: New Insights from Afro-Peruvian Spanish - Sandro Sessarego; Javier Gutiérrez-Rexach (Isogloss, 2017)
With the advent of the Minimalist Program (Chomsky 1995), the prevailing view of linguistic variation and contrast within universal Grammar has undergone a shift from rigidly defined parameters ˗associated with clusters of properties (Chomsky 1981; Chomsky & Lasnik 1993)˗ to an approach in which features play a central role, are flexibly distributed, and originate in the lexicon, according to what Baker (2008) calls the "Borer-Chomsky conjecture" (Borer 1984; Chomsky 2001). A closer cross linguistic look at empirical data seems to support this change in focus. The Null Subject Parameter (NSP) (Chomsky 1981; Rizzi 1982), as originally formulated, had a number of shortcomings (cf. Huang 1994; Holmberg 2005). Within the realm of Spanish and Portuguese, two dialects that do not follow the predictions of the NSP are Dominican Spanish (DS) and Brazilian Portuguese (BP). The analysis of these varieties has led to the postulation of new hypotheses to account for their unexpected syntactic patterns (cf. Duarte 1993; Toribio 2000; Camacho 2008; etc.). The present study pays attention to yet another dialect of Spanish that does not conform to the NSP, Chinchano Spanish (CS), an Afro-Hispanic variety spoken in Chincha, Peru. In so doing, this paper provides an analysis of null and overt subjects that partially deviates from previous accounts of similar pro-drop phenomena. Additionally, this study proposes a model of contact-induced language transmission that explains why CS –as well as many other Afro-Hispanic languages of the Americas (AHLAs)– presents patterns that do not align this dialect with either null-subject languages (NSLs) like Italian or non-null-subject languages (NNSLs) like English.